Notes on helminth parasites of tuna fishes (Scombridae) in Brazil - Márcia Cristina Nascimento-Justo; Anna Kohn (Revista Mexicana de Biodiversidad)
Four species of Scombridae from the coast of Rio de Janeiro, southwest Atlantic Ocean were found to be parasitized with species of Didymozoidae (Digenea): Thunnus atlanticus (Lesson) a new host record for Nephrodidymotrema ahi Yamaguti, 1970, Didymocystis neothunni (Yamaguti, 1970), and Didymozoon longicolle (Yamaguti, 1970); Thunnus obesus (Lowe) parasitized by Didymozoon longicolle and reported as a new host for Nephrodidymotrema ahi; Thunnus albacares (Bonaterre) parasitized by Nephrodidymotrema ahi, and Katsuwonus pelamis (Linnaeus) by Didymozoon longicolle. Measurements, figures, and parameters of infection are presented.